Terumbu Karang Taman Wisata Perairan Pulau Pieh Sumatera Barat - Dian Sutono HS; Syamsul Bachri Lubis (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2018)
The Marine Conservation Area (MCA) of the Marine Tourism Park of Pieh and the Surrounding Islands, consists of Bando Island, Pieh Island, Air Island, Toran Island and Pandan Island with covering of ​​39,900 Ha wide. Geographically Pieh Island is at coordinates 00⁰ 45’ 10